2014
DOI: 10.1103/physreve.89.043305
|View full text |Cite
|
Sign up to set email alerts
|

Accurate solution of the Dirac equation on Lagrange meshes

Abstract: The Lagrange-mesh method is an approximate variational method taking the form of equations on a grid because of the use of a Gauss quadrature approximation. With a basis of Lagrange functions involving associated Laguerre polynomials related to the Gauss quadrature, the method is applied to the Dirac equation. The potential may possess a 1/r singularity. For hydrogenic atoms, numerically exact energies and wave functions are obtained with small numbers n + 1 of mesh points, where n is the principal quantum num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…The potential matrix is then diagonal and only involves values of the potential at mesh points. Recently, we have shown that numerically exact solutions of the CoulombDirac equation can be obtained with this method [12,13]. More generally, the method is very accurate for most central potentials as illustrated with Yukawa potentials in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The potential matrix is then diagonal and only involves values of the potential at mesh points. Recently, we have shown that numerically exact solutions of the CoulombDirac equation can be obtained with this method [12,13]. More generally, the method is very accurate for most central potentials as illustrated with Yukawa potentials in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This can be improved by replacing the Lagrange-Legendre basis in the internal region by an appropriate Lagrange-Jacobi basis [18], in the same spirit as done for bound states in Ref. [27]. With a Laguerre mesh in the external region, no restriction is needed on the potential in bound-state calculations.…”
Section: Resultsmentioning
confidence: 99%
“…This nonorthogonal basis is treated as orthonormal [18]. Using the Gauss-Legendre quadrature for the calculation of integrals [18,27]…”
Section: Lagrange-mesh Methods Over the Internal Regionmentioning
confidence: 99%
See 2 more Smart Citations